Penguatan Manajemen SDM dalam Peningkatan Kapasitas Koperasi dan UMKM di Kabupaten Bogor: Penguatan Manajemen SDM dalam Peningkatan Kapasitas Koperasi dan UMKM di Kabupaten Bogor - Muslim, Bukhari (The Manager Review, 2025)
Cooperatives and Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economic development, including in Bogor Regency. However, limited human resource (HR) capacity remains a major challenge in improving business competitiveness and sustainability. This study aims to analyze the strengthening of human resource management in enhancing the capacity of cooperatives and MSMEs in Bogor Regency. The research employs a descriptive quantitative approach using secondary data from the Central Bureau of Statistics (BPS) of Bogor Regency for the period 2023–2025 and primary data collected through questionnaires distributed to cooperative managers and MSME actors. The results indicate that HR planning, training and competency development, and the implementation of digital-based HR management practices have a positive contribution to improving business capacity, as reflected in increased productivity, operational efficiency, and adaptability to market changes. This study highlights that strengthening human resource management is a key factor in promoting more competitive and sustainable cooperatives and MSMEs in the digital era.